Clinical features and outcomes of hospitalized patients with COVID-19 during the Omicron wave in Shanghai, China. Issue 1 (January 2023) - Wang, Bin; Yu, Yuefeng; Yu, Yuetian; Wang, Ningjian; Chen, Fengling; Jiang, Boren; Chen, Yi; Zhang, Junfeng; Liu, Jianren; Wang, Haiya; Ding, Feng; Zhang, Wenchuan; et al.
Abstract : Hospitalized patients with Omicron infection revealed a mild severity of disease. The in-hospital outcomes were affected by vaccination status and morbidity condition. Severe outcomes concentrated in the elderly who were unvaccinated or had comorbidity. Unvaccinated patients had a lower negative conversion rate than vaccinated patients.